Role of Chlamydia trachomatis in Miscarriage - Baud, David (Centers for Disease Control and Prevention, 2011)
To determine the role of Chlamydia trachomatis in miscarriage, we prospectively collected serum, cervicovaginal swab specimens, and placental samples from 386 women with and without miscarriage. Prevalence of immunoglobulin G against C. trachomatis was higher in the miscarriage group than in the control group (15.2% vs. 7.3%; p = 0.018). Association between C. trachomatis–positive serologic results and miscarriage remained significant after adjustment for age, origin, education, and number of sex partners (odds ratio 2.3, 95% confidence interval 1.1–4.9). C. trachomatis DNA was more frequently amplified from products of conception or placenta from women who had a miscarriage (4%) than from controls (0.7%; p = 0.026). Immunohistochemical analysis confirmed C. trachomatis in placenta from 5 of 7 patients with positive PCR results, whereas results of immunohistochemical analysis were negative in placenta samples from all 8 negative controls tested. Associations between miscarriage and serologic/molecular evidence of C. trachomatis infection support its role in miscarriage.